Analisis Kesulitan Membaca Permulaan Peserta Didik Kelas I Di SDN 26 Ampenan - Aulia Azizah Rahman; Darmiany Darmiany; Ketut Sri Kusuma Wardani (Journal of Classroom Action Research, 2023)
This study aims to analyze various beginning reading difficulties experienced by students, to find out the factors that hinder students in beginning reading difficulties, and to find out solutions to overcome students' initial reading difficulties in grade I SDN 26 Ampenan. This research is a qualitative descriptive study. This research was conducted at SDN 26 Ampenan involving grade 1 students at SDN 26 Ampenan. Data collection techniques in this study are using interviews, observation and documentation. The results showed that 47.6% of the subjects had difficulty reading at the beginning. Based on these results, it can be seen that the initial reading level of class I students at SDN 26 Ampenan is classified as "Not Good". The difficulties that students often encounter include: 1) difficulty recognizing letters, 2) difficulty reading words, 3) reading words that have no meaning, and 4) fluency in reading aloud and reading comprehension. Factors that influence these difficulties include a lack of interest in learning subjects, subjects not attending kindergarten and lack of family support in reading. The solutions implemented by the teacher to overcome the subject's problems in Beginning Reading Difficulties in grade I at SDN 26 Ampenan are; 1) the teacher holds additional hours for students who still have difficulty reading at the beginning, 2) the teacher pays more and special attention to subjects who still cannot read at the beginning, 3) letters are used as singing material, and 4) displays letters and discusses their shape (characteristics) especially letters that have a similar shape (for example p, b, d, m, and n).